Downregulation of vitamin D receptor and miR‐126‐3p expression contributes to increased endothelial inflammatory response in preeclampsia. (17th August 2019) - Xu, Jie; Gu, Yang; Lewis, David F.; Cooper, Danielle B.; McCathran, Charles E.; Wang, Yuping
Abstract: Problem: To investigate whether downregulation of miR‐126‐3p and vitamin D receptor (VDR) expression contributes to increased endothelial inflammatory response in preeclampsia. Methods of study: Maternal vessel miR‐126‐3p expression was assessed by in situ hybridization. VDR expression and VCAM‐1 expression were determined by immunostaining. Subcutaneous adipose tissue sections from normotensive and preeclamptic pregnant women were used. HUVECs from normotensive deliveries were used to test anti‐inflammatory effects of vitamin D and miR‐126‐3p in endothelial cells (ECs) treated with TNFα in vitro. 1, 25(OH)2 D3 was used as bioactive vitamin D. Transient overexpression of miR‐126‐3p in ECs was induced by transfection of pre‐mir‐126 precursor. Endothelial VCAM‐1 and SOCS‐3 expression or production was determined by Western blotting or by ELISA, respectively. Results: Reduced VDR and miR‐126‐3p expression, but increased VCAM‐1 expression, was observed in maternal vessel endothelium in tissue sections from women with preeclampsia compared to normotensive pregnant controls. Transient overexpression of miR‐126‐3p not only attenuated upregulation of VCAM‐1 expression and production, but also preserved downregulation of SOCS‐3 expression, induced by TNFα in ECs. VDR expression and miR‐126‐3p expression were significantly upregulated in cells treated with 1, 25(OH)2 D3, but not in cells transfected with VDR siRNA. Conclusion: Downregulation of VDR and miR‐126‐3p expression was associated with upregulation of VCAM‐1 expression in systemic vessel endothelium in preeclampsia. The finding of increased anti‐inflammatory property by 1, 25(OH)2 D3 through promotion of VDR and miR‐126‐3p expression in ECs provide plausible evidence that vitamin D deficiency and downregulation of VDR expression could contribute to increased inflammatory phenotypic changes in maternal vasculature in preeclampsia.